Adaptation and Evaluation of Portable Gun Type Sprinkler Irrigation for Smallholder Farmers (American Journal of Agricultural Science, Engineering, and Technology, 2023)
The effectiveness of irrigation water management practices can be based on the uniformity and efficiency of the irrigation system. The water must be applied uniformly over the field. The study was conducted to fabricate and evaluate rain gun sprinkler irrigation by two factors of treatments on throwing distance, precipitations water depth and distribution uniformity. The three-nozzle sizes of Ø6mm, Ø8mm and Ø10mm were used as one factor of treatment and three pressure gauges 4bar,3bar and 2bar were used the second factor of treatment during prototype evaluation and operation. From the result, all of the interaction effects of different nozzle size and pressure gauge on throwing distance were significantly different from each other’s. The interaction effect of 10NS*4PG was the highest value of 40.32 m. The next was the interaction effect of 8NS*4PG that has 39.19 m, but it did not have significant different with 6NS*45PG and its values 38.83 m. For precipitation water depth the maximum result was obtained during interaction effect of 10NS*4BPG and next was 8NS*4BPG. The highest water distribution uniformity was seen at the interaction effect of 6NS*4BPG and its value of 80.77%. But did not significantly different with the interaction effect of 6NS*3BPG and its value of 78.63%. The interaction effect of 8NS*4BPG has second-rank interims of three evaluation parameters of throwing distance, precipitation water depth and distribution uniformity value of 39.19m,26.10mm/mint and 74.9% respectively. So it is recommended to use the interaction effect of 8NS*4BPG for the three-inch water pump.